El Excentrico, 1960-04-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
April 5, 1960 [5 de abril de 1960]. Ano 10, No 14. Cover has photograph of three women holding a conventional oven for an advertisement with headline "Menudo - Tamale Sale."